The Effect of Nano Sized TiO2 Particles on Improving the Stress Resistance and Thermal Stability of Unsaturated Polyester - Rana J. Mizban; Widad H. Jassim (Ibn Al-Haitham Journal for Pure and Applied Sciences)
An unsaturated polyester's (UPE) mechanical and thermal properties were modified by incorporating nanosized titanium dioxide (TiO2) particles with 1, 2, 3, 4, and 5% weight ratios. 3% of TiO2 is the best weight percentage that can be added to UPE to improve its impact strength from 8.74 MPa to 8.87 MPa, its hardness value from 82.23% to 86.63%, its tensile strength from 7.698 MPa to 24.76 MPa, and its thermal conductivity from 0.308499 W/m.oC to 0.566916 W/moC. Also, the thermal stability of UPE/3% TiO2 was improved using thermogravimetric analysis (TGA). XRD measurement was employed to verify the change caused by adding TiO2 particles to the internal structure of unsaturated polyester. Also, the change in the microstructure of unsaturated polyester after adding TiO2 nanoparticles was studied using scanning electron microscope analysis, where the TiO2 nanoparticles showed a good distribution in the matrix, and the TiO2 had good compatibility in the unsaturated polyester matrix.